Déjà vu As an Incarnation of the Human Consciousness of Time: A Reading in T.S. Eliot's "Burnt Norton" and Dylan Thomas's "Fern Hill" - Mousa, Shubbar Abdul Adil (Tasnim International Journal for Human, Social and Legal Sciences, 2024)
The aim of this study is to examine the Déjà vu, that is the sensation of having previously encountered something. It is a prevalent occurrence that has captivated several authors and artists throughout history. Literature has examined this issue via many approaches and provided a diversity of assimilations for the concept of time. Both T.S. Eliot's "Burnt Norton" and Dylan Thomas's "Fern Hill" poems use this concept to illustrate the impact of Time on the human experience, as they emphasize the human consciousness in the recurring pattern of Time and how people's recollections of the past may influence their current and future circumstances. In "Burnt Norton," Eliot used the garden metaphor to express the sensation of Déjà vu. The speaker recounts his previous visit to the garden but cannot recall when and where it occurred. He has a sensation of reexperiencing a former event, which causes him to feel uneasy. The speaker is keenly aware of the perpetual progression of Time and the irrevocable nature of the past. This revelation exacerbates his uneasiness since he perceives himself incapable of evading the perpetual cycle of Time. Similarly, in "Fern Hill," Thomas depicted a childhood recollection to communicate Time's recurring and repetitive essence. The speaker recounts his recollections of summer vacation on a farm and elucidates how those reminiscences have become entwined with his current reality. He has a sensation of repeating his childhood events, and this feeling of Déjà vu evokes nostalgia and a yearning for a more uncomplicated era. Thomas proposes that our recollections of the past may elicit both solace and anguish, serving as poignant reminders of the things people have lost as well as what people will never reclaim. Both Eliot and Thomas use Déjà vu to underscore the influence of Time on the human condition. They propose that a straight progression does not characterize Time but instead follows a recurring pattern. They argue that recollecting previous events may significantly influence our current and future experiences that unfold the stream of consciousness. The topic of Déjà vu also emphasizes the constraints of human comprehension since we cannot completely grasp the intricacies of Time and the world.